Species Diversity of the Pleurostomatid Ciliate Genus Amphileptus (Ciliophora, Haptoria), With Notes on the Taxonomy and Molecular Phylogeny of Three Species - Wu, Lei; Li, Jiqiu; Warren, Alan; Lin, Xiaofeng (Frontiers in Marine Science, 2021)
Amphileptus is one of the largest genera of pleurostomatid ciliates and its species diversity has been reported in various habitats all over the world. In the present work, we review its biodiversity based on data with reliable morphological records. Our work confirms that there are 50 valid Amphileptus species, some of which have a wide range of salinity adaptability and diverse lifestyles. This genus has a high diversity in China but this might be because of the relatively intensive sampling. Phylogenetic analyses based on SSU rDNA sequence data verify the non-monophyly of the genus Amphileptus. Furthermore, two new and one poorly known Amphileptus species, namely A. shenzhenensis sp. n., A. cocous sp. n., and A. multinucleatusWang, 1934, from coastal habitats of southern China were investigated using morphological and molecular phylogenetic methods. These three species are highly similar based on their contractile vacuoles and macronuclear nodules. However, they can be discriminated by details of their living morphology and somatic kineties. We also propose two new combinations, Amphileptus polymicronuclei (Li, 1990) comb. n. (original combination Hemiophrys polymicronucleiLi, 1990) and Amphileptus salimicus (Burkovsky, 1970b) comb. n. (original combination Hemiophrys salimicaBurkovsky, 1970b).